MODAL SOSIAL SEBAGAI UPAYA KEBERLANGSUNGAN USAHA DITENGAH PANDEMI COVID-19 (STUDI KASUS PADA DEBITUR ULTRA MIKRO (UMI) PT. PEGADAIAN (PERSERO) AREA LAMPUNG) - Aprilia, Rini Aprilia; Gunarto, Toto; Taher, Arivina Ratih Yanti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.08.TAHUN.2021DO - 10.24843/EEB.2021.v10.i08.p02, 2021)
The Covid-19 pandemic has not only impacted the health sector, but also in the economic and social sectors. Social restrictions and decreased purchasing power of the community led to a decrease in economic activity, especially lower-layer businesses or so-called ultra-micro enterprises. In addition to stimulus or physical capital, social capital is also required for a business s ustainability. Social capital is conceptually a relational relationship obtained from social interaction between ultra-micro enterprise. Trust indicates that there is a network that shows a link between individuals or groups that interact with each other continuously so that a trust between members is formed. The network that generates benefits that lead to interdependence between members. Values and norms become the basis of the formation of social capital because it becomes the basis in the formation of a reciprocal relationship between individuals or groups. The elements contained in social capital that has the potential to be the efforts of businesses in maintaining their business. Respondents in this study numbered 85 customers, selected using random sampling. Hypothesis testing is conducted with multiple regression analysis. The results of this study are social capital positive and significant influence on the business sustainability of ultra micro debtors PT. Pegadaian (Persero) area Lampung .